What does your workplace say about your company culture? - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2016)
Disengagementin the workplace can create toxic environments – research has linked suchdisengagement with decreased client interactions and reduced collaborativeperformance, increased absenteeism, and a rise in workplace harassment. Arecent State of the American Workplace study conducted byGallup estimated that active disengagement in the workplace costs the UnitedStates between US$450 billion and US$550 billion annually.